(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The purpose of this article is to present the structure, functioning, and results of the EMPACT platform in the field of cybercrime, which has a prominent role in international criminal cooperation and is now a permanent EU instrument. Methodology: The Author collected knowledge about the EMPACT platform by examining the available EU legislation and by performing in practice the tasks of a former expert in the cyber-attacks priority and the current deputy national EMPACT coordinator. Findings: In the fight against serious and organized crime, the Member States, and countries with close links to the EU can carry out their tasks effectively by working together and making the greatest possible use of legal, technical, and educational resources. The permanent EU instrument provides both operational and strategic support for the participants. Value: The study provides a comprehensive overview of this area of international criminal cooperation, which will help law enforcement and judicial authorities to gain a deeper insight into the practical implementation of the task, and will provide interested parties with contextualised answers about the steps and processes involved.